Effects of Professionalism, Organizational Commitment, and Technology on Auditor Performance Mediated by Quality Culture - Tri Purnomo Ariadi; Trinandari Prasetya Nugrahanti (International Journal of Economics, Business and Innovation Research, 2026)
This study investigates the effects of professionalism, organizational commitment, and information technology (Pentana Audit) on auditor performance, with quality culture as a mediating variable. A quantitative research approach was employed, involving 78 auditors of the Inspectorate of the Corruption Eradication Commission (KPK) as respondents, using a saturated sampling technique. Data were collected through an online questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3 software. The findings reveal that professionalism, organizational commitment, and information technology have positive and significant effects on quality culture. Furthermore, professionalism and organizational commitment significantly enhance auditor performance, while information technology does not have a direct significant effect on auditor performance. Quality culture, however, has a positive and significant influence on auditor performance. Importantly, quality culture is proven to mediate the relationships between professionalism, organizational commitment, information technology, and auditor performance. These results highlight the crucial role of quality culture in strengthening auditor performance.